ASSESSMENT OF THE PB-PB AND U-PB CHRONOMETRY OF THE EARLY SOLAR SYSTEM - II. MAGNESIUM - Tera F.; Carlson R.W. (My University, 1999)
An evaluation of early solar system chronometry by the Pb-Pb and U-Pb methods is provided. Specifically, three consequential factors are examined: procedure of age calculation, extent of terrestrial Pb contamination, and initial Pb isotopic composition. On a Pb-Pb diagram, high temperature inclusions of the Allende meteorite are tightly organized into a well-defined line (inside a potentially dispersive mixing field), which is consistent with the inclusions containing initial Pb that is more primitive than that of Canon Diablo troilite (PAT). Consequences of the possible existence of a pre-PAT Pb to the evolution history of the solar nebula are discussed.Phosphates from the ordinary chondrite St. Severin appear to be contaminated by terrestrial Pb, a condition that renders age calculation based on subtraction of PAT inaccurate. The Pb-Pb mixing line of these phosphates indicates an age of 4.558 Ga. Interestingly, Angra dos Reis phosphate and pyroxene, as well as pyroxene of the other angrite Lewis Cliff 86010 fall precisely on the line defined by St. Severin phosphates.Whole rocks of ordinary chondrites are pictorially and explicitly shown to be seriously contaminated with terrestrial Pb, thus their single-stage U-Pb ages may not be suitable markers of time. Because their true crystallization ages are often younger than the whole rocks, and because of the possibility of multistage evolution, phosphates of ordinary chondrites may yield single-stage ages older than their true crystallization ages. A hypothetical numerical demonstration is provided.On the basis of revised ages and new observations we provide an ''updated'' chronometry for the early solar system.